Zika virus infection in pregnant travellers and impact on childhood neurodevelopment in the first two years of life: A prospective observational study. Issue 40 (March 2021) - Marbán-Castro, Elena; Goncé, Anna; Fumadó, Victoria; Martínez, Miguel J.; López, Marta; García-Otero, Laura; Salazar, Laura; Esteve, Carolina; Salvia, Dolors; Fortuny, Claudia; Eixarch, Elisenda; Fuente-Moreno, Marina; et al.
Abstract: Background: The emergence of Zika virus (ZIKV) represents a threat with consequences on maternal and children's health. We aimed to assess the clinical and epidemiological characteristics of pregnant women returning from ZIKV affected areas, and the effects of maternal ZIKV infection on birth outcomes and children's health. Methods: This was a hospital-based prospective observational study conducted at the Hospital Clínic of Barcelona and Hospital Sant Joan de Déu, Barcelona, Spain, from January 2016 to February 2020. Results: One hundred and ninety-five pregnant women who had travelled to ZIKV affected areas during pregnancy were recruited. Four women (2.1%) had a confirmed ZIKV infection, 40 women (20.5%) a probable infection, and 151 (77.4%) were negative for ZIKV. Among the ZIKV confirmed cases, a pregnant woman suffered a miscarriage, highly plausible to be associated with ZIKV infection. Brain cysts and microcalcifications were detected in 7% of fetuses or infants from women with confirmed or probable ZIKV infection. Neurodevelopmental delay in the language function was found in 33.3% out of the 21 children evaluated. Conclusions: These findings contribute to the understanding of ZIKV prevalence estimates, and the impact of maternal ZIKV infection on pregnancy outcomes and children's health. Results highlight the importance of long-term surveillance in pregnant travellers and their children. Highlights: Pregnant travellers to ZIKV endemic areas are at risk of acquiring ZIKV infection and suffering consequences on pregnancy. ZIKV infection is associated with poor pregnancy outcomes such as miscarriage. Exposure to ZIKV in uterus is associated with neurodevelopmental impairment. Language function is the most affected domain in children's neurodevelopment.